2020
DOI: 10.1177/1540415320956389
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Access to Care in Hispanics With Type 2 Diabetes: A Systematic Review

Abstract: Introduction: Type 2 diabetes (T2D) is a major cause of death in the United States. Hispanics living in America suffer disproportionally with diabetes and is the fifth cause of death for them. A systematic review was conducted that highlighted barriers to access to care for Hispanics with T2D during the early years of the Affordable Care Act. Method: PubMed and CINAHL databases were searched (2010-2015) using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) guidelines. From 84 studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Standard of care as the main approach to treat and prevent T2D globally can be expensive for patients globally as these methods often require follow up appointments, which can lead to having to take time off of work and travel far distances (Mohan et al, 2019). Further, primary care might have long wait times for appointments and specialized physicians may not be available when needed (Titus et al, 2020). Accessibility is further limited by insurance willingness to cover visits, especially in the U.S. (Titus et al, 2020).…”
Section: Significance Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard of care as the main approach to treat and prevent T2D globally can be expensive for patients globally as these methods often require follow up appointments, which can lead to having to take time off of work and travel far distances (Mohan et al, 2019). Further, primary care might have long wait times for appointments and specialized physicians may not be available when needed (Titus et al, 2020). Accessibility is further limited by insurance willingness to cover visits, especially in the U.S. (Titus et al, 2020).…”
Section: Significance Of Resultsmentioning
confidence: 99%
“…Further, primary care might have long wait times for appointments and specialized physicians may not be available when needed (Titus et al, 2020). Accessibility is further limited by insurance willingness to cover visits, especially in the U.S. (Titus et al, 2020). Digital delivery of lifestyle interventions is a portable option of care and is available at any time when the patient is available.…”
Section: Significance Of Resultsmentioning
confidence: 99%
“…Another major concern is being able to fully understand genetic susceptibility in a society where access to healthcare significantly contributes to health disparities. A recent review of Hispanics/Latinos with type 2 diabetes found that cost, time, and lack of social support are among the barriers that prevent these populations from seeking and receiving the care they need (Titus and Kataoka-Yahiro 2021 ). Research conclusions must be carefully phrased to avoid claims that a certain population is more genetically predisposed than others, particularly because health risks can be compounded and such claims could have social and legal implications, especially for disadvantaged communities.…”
Section: Polygenic Score (Pgs) Challenges and Future Directionsmentioning
confidence: 99%
“…Patients who experience one or more of these barriers are more likely to resort to emergency care. [22][23][24] Furthermore, language barriers, cultural incompetence, ineffective communication, and lack of patient involvement in the decision-making process are barriers to seeking preventive health care services, screenings, and palliative or hospice care and adhering to therapy. 22,[25][26][27][28] Patients with LEP who have difficulty reading, understanding, writing, or speaking English are more likely to have poor outcomes and poor drug adherence.…”
Section: Disparities In Health Carementioning
confidence: 99%